A kinetics-mass transport model for CO2 electroreduction reactor to investigate performance limitation factors. (23rd November 2022) - Fang, Yuanxin; Cui, Haozhe; Chen, Bo; Chen, Wanting; Ruan, Xuehua; Wu, Xuemei; Cui, Fujun; Guo, Minggang; He, Gaohong
Graphical abstract: Highlights: A novel kinetics-mass transport model for CO2 electroreduction reactor is proposed. CO2 RR-HER competition, selectivity-conversion, H2 utilization link to key parameters. The model is embedded into Aspen HYSYS to provide process design tool for CO2 ECR. Abstract: Modeling of CO2 electroreduction reactor (CO2 ECR) is highly demanded for rapid design of industrial processes, while facing challenges in practical applications. Herein, a kinetics-mass transport model is proposed, which can well balance the competition between HCOO – produce and H2 evolution, and be easily integrated into Aspen HYSYS as a user defined module for CO2 ECR process design. By considering both cathode potential and CO2 concentration in flow channel, optimal regions of the key parameters can be simulated to achieve high efficiency of CO2 electroreduction, i.e., about 80 % for both HCOO – Faraday efficiency and CO2 conversion with slightly compressed pure CO2 feedstock of 300 kPa. By increasing anode flow rates, the lean streams with H2 concentration of around 50% achieve nearly the maximum H2 utilization, which is attractive due to the possible reduction of purification cost.